Unmasking (New) Maternal Realities
XXI, 295 p. 35 illus.
Keywords: “The volume is an important contribution to a humanities-based approach to motherhood studies. The essays included in this impressive volume, rooted in maternal feminism, encompass a remarkable range of materials from different cultural, national, and linguistic traditions. The variety of narrative forms examined—novels, memoirs, social media posts, films, and auto-ethnographies—demonstrate how experiences of motherhood and its aftermath are not simply the source of ‘a new literary genre,’ but inspire daring experimentation and innovation.” —Giovanna Faleschini Lerner, Professor of Italian, Program Chair of Comparative Literary Studies, Franklin & Marshall College, USA “This collection includes essays on pregnancy, the different forms and settings of birth, and postpartum experiences such as postpartum psychosis and lactation following the loss of the baby. Featuring work by established academics and emerging scholars alike, the volume offers a fresh view on many issues explored by motherhood studies making it essential reading for everyone interested in motherhood and feminist studies.” —Eglė Kačkutė, Professor of French Literature and Gender Studies, Vilnius University, Lithuania, and Coordinator of the MotherNet Network This book aims to shed light on artistic works centered on mothering and reproductive experiences, ones which defy outdated stereotypes, break taboos, overcome trauma, and empower women. The goal of this collection is to contribute to this field of studies and foster our understanding of what motherhood and mothering really look like in our society. Throughout this collaborative volume, the voices of established and emerging scholars merge to broaden the discourse on maternity by examining the complex and constantly evolving maternal experiences that are unique and yet transnational and universal in their essence. Laura Lazzari is a Scientific Collaborator at the Sasso Corbaro Foundation for the Medical Humanities, Switzerland, and an Affiliate Faculty and Scholar at Georgetown University, USA. Giulia Po DeLisle is Associate Professor and Coordinator of Italian Language and Culture at the University of Massachusetts Lowell, USA.